Demonstrating development: meetings as management in Kenya's health sector. (16th March 2017) - Brown, Hannah; Green, Maia
Abstract : International development operates as a system of meetings. This essay shows how meetings work within aid regimes to structure responsibilities for implementation, to situate projects within funding streams, and to realize the effects of scale. Where donor aid is increasingly allocated to support national plans which are the responsibility of recipient governments, the monitoring of outcomes requires the instantiation of project forms within and across existing state institutions. This involves the delineation of distinct sectors and their scale of operation, alongside the maintenance of relations with external funders. Drawing on ethnographic material from the Kenyan health sector, we show how development projects are realized as tangible social institutions through the structure of formal meetings. Meetings mark the temporality and trajectory of development as a set of planned activities contributing to specific targets. In the context of specific projects they become fora where commitment to development goals of participation, capacity‐building, and effective management can be demonstrated.